Comparative Assessment of 0.5% Levobupivacaine and 0.5% Ropivacaine for Anaesthetic Potency in Mandibular Third Molar Extractions: A Randomised Controlled Trial - Prachi Surolia; Rajanikanth Kambala; Nitin Bhola; Anchal Agarwal (Journal of Clinical and Diagnostic Research)
Introduction: Patients often experience postoperative pain for more than 24 hours after the extraction of impacted mandibular third molars. This has led to the consideration of using long-acting anaesthetic drugs to alleviate patients’ discomfort. However, there is no conclusive evidence comparing the anaesthetic efficacy of long-acting anaesthetic drugs such as Levobupivacaine and Ropivacaine in impacted mandibular third molar surgery. To address this gap, a study was conducted to compare these two drugs in the context of oral and maxillofacial surgery for third molar extraction. Aim: To evaluate and compare the anaesthetic effectiveness of 0.5% Levobupivacaine and 0.5% Ropivacaine in impacted mandibular third molar surgery. Materials and Methods: A prospective, randomised, triple-blind trial was conducted in the Department of Oral and Maxiilofacial Surgery at Sharad Pawar Dental College and Hospital, Datta Meghe Institute of Higher Education and Research, Wardha, Maharashtra, India from November 2023 to May 2024 on 60 healthy patients, aged 18-40 years, who required extraction of an impacted mandibular third molar, were included in the study. The patients were divided into two groups; Group A and B were anaesthetised locally using 0.5% Levobupivacaine, and 0.5% Ropivacaine, respectively. The study assessed and compared latency, depth of anaesthesia, and time to rescue analgesia. Statistical analysis was performed using descriptive and inferential statistics, including the Student’s unpaired t-test for intergroup comparison and Fisher’s-exact test to assess the non random association between two categorical variables. A p-value of <0.05 was considered significant for interpreting the results. Results: The mean age of subjects in the study sample was 27.26±6.13 years in Group B and 27.23±5.24 years in Group A. The study found that Levobupivacaine demonstrated a faster onset of anaesthesia (104.06 seconds) compared to Ropivacaine (192.33 seconds), with a significant difference (p=0.0001). Both Levobupivacaine and Ropivacaine showed similar efficacy in achieving the depth of anaesthesia during surgery, with no statistically significant difference observed (p=1.00). The Levobupivacaine group exhibited a longer time to rescue analgesia (656.50 minutes) compared to the Ropivacaine group (501.83 minutes), with a statistically significant difference (p=0.0001). Conclusion: A 0.5% Levobupivacaine provides a quicker onset of anaesthesia and a longer duration of pain relief compared to 0.5% Ropivacaine, with a comparable depth of anaesthesia in both groups. Clinicians could consider using 0.5% Levobupivacaine to provide early onset of anaesthesia, prolonged pain relief, and greater postoperative comfort for the patients.